Uncertain powers : Sen'yōmon-in and landownership by royal women in early medieval Japan - Kawai, Sachiko (Harvard East Asian monographs, 2021)
"Explores the important political and economic leadership roles of royal women in medieval Japan, questioning the traditional view of the era as one dominated by male retired monarchs and warrior government. These women, who held the title of premier royal lady (nyoin), owned extensive landed estates across Japan, and used their wealth and networks to build temples and to assert religious, cultural, and political influence"--